Regenerating Japan : organicism, modernism and national destiny in Oka Asajiro's Evolution and human life - Sullivan, Gregory (Gregory F.) (Budapest ; New York : Central European University Press, 2018)
"As the first step toward a comprehensive reinterpretation of the role of evolutionary science and biomedicine in pre-1945 Japan, this book addresses the early writings of that era's most influential exponent of shinkaron (evolutionism), the German-educated research zoologist and popularizer of biomedicine, Oka Asajiro (1868-1944). Concentrating on essays that Oka published in the years during and after the Russo-Japanese War (1904-5), the author describes the process by which Oka came to articulate a programmatic modernist vision of national regeneration that would prove integral to the ideological climate in Japan during the first half of the twentieth century. In contrast to other scholars who insist that Oka was merely a rationalist enlightener bent on undermining state Shinto orthodoxy, Gregory Sullivan maintains that Oka used notions from evolutionary biology of organic individuality--especially that of the nation as a super-organism--to underwrite the social and geopolitical aims of the Meiji state. The author suggests that this generative scientism gained wide currency among early twentieth-century political and intellectual elites, including Emperor Hirohito himself, who had personal connections to Oka. The wartime ideology may represent an unfinished attempt to synthesize Shinto fundamentalism and the eugenically-oriented modernism that Oka was among the first to articulate"--
Introduction : moss animal nation -- The organic state : the imperative of ethical life -- Palingenetic polypersons : evolutionary morphology and the question of organic individuality -- Generative scientism : organicism beyond reform -- World War Zero -- The human-way : nomic instincts and the transformation of humanity -- Nomic crisis -- Decadence and destiny -- Epilogue : evolution and the national body : an unfinished synthesis.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on November 27, 2018).
JSTOR
Keywords: Oka, Asajirō, -- 1868-1944.; Oka, Asajirō, -- 1868-1944.; Biology -- Social aspects -- Japan; Biology -- Study and teaching -- Japan; Evolution (Biology) and the social sciences -- Japan; Biologie -- Aspect social -- Japon; Biologie -- Étude et enseignement -- Japon; NATURE -- Reference; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- General; HISTORY -- Asia -- Japan; Biology -- Social aspects; Biology -- Study and teaching; Evolution (Biology) and the social sciences; Japan